Acceleration slope of exercise-induced impacts is a determinant of changes in bone density - Heikkinen, Riikka; Vihriälä, Erkki; Vainionpää, Aki; Korpelainen, Raija; Jämsä, Timo (Journal of biomechanics, 2007)
High acceleration levels (>4 g) seen during impact exercises have been shown to increase bone mineral density (BMD) in premenopausal women. The aim of this study was to examine how the other acceleration signal characteristics, i.e. the slope, area and energy of the signal are related to changes in bone density, using long-term quantification of physical activity. Daily physical activity was continuously assessed with a waist-worn accelerometer-based body movement monitor in 64 premenopausal women participating in a 12-month population-based exercise trial. The daily number of exercise-induced impacts at different slope, area and energy levels of the acceleration signal was analyzed. Physical activity inducing slopes ⩾1000 m/s 3, acceleration peak areas ⩾2 m/s or signal energies ⩾75 m 2/s 3 was associated with BMD change in the hip ( p<0.05). Impacts with the smallest slopes (<1000 m/s 3) were positively associated with changes in calcaneal speed of ultrasound, while impacts with slopes ⩾1500 m/s 3 or areas ⩾4 m/s were positively correlated with broadband ultrasound attenuation changes ( p<0.05). We conclude that the acceleration slope of exercise-induced impacts is an important determinant of bone density. The slope threshold for improving BMD at the hip is 1000 m/s 3, which can be achieved during normal exercise including fast movements such as running and jumping.